1992
DOI: 10.1007/bf00195326
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol stimulates phospholipid turnover and inositol 1,4,5-trisphosphate production in Chlamydomonas eugametos gametes

Abstract: Abstract. Alcohols induce mating-structure activation inChlamydomonas eugametos gametes. From the effect of ethanol on the 32p-labelling of polyphosphoinositides, we conclude that the synthesis of these lipids is stimulated. Biologically inactive concentrations of ethanol (<6%) had no effect on synthesis, but 6-8% ethanol stimulated synthesis for upto 60 min. The 32p incorporated into polyphosphoinositides and phosphatidic acid during ethanol treatment was readily chased out when 1 mM unlabelled Na3PO4 was add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…In animal systems, the hydrolysis of PtdInsP 2 by phospholipase C is reflected in a rapidly 32P-labelled PtdOH pool due to subsequent phosphorylation of the resulting DAG by DAG kinase (Berridge 1992). Similar claims have been made for the green algae Chlamydomonas and Dunaliella (Einspahr et al 1988;Brederoo et al 1991 ;Ha and Thompson1991 ;Musgrave et al 1992) and the same process is presumed to occur in higher plants (Heim and Wagner 1990). In carnation, the rapid incorporation and loss of 32p-label from PtdOH resembles the labelling kinetics of PtdInsP and PtdInsP2, suggesting that the two are again causally related.…”
Section: Discussionmentioning
confidence: 68%
“…In animal systems, the hydrolysis of PtdInsP 2 by phospholipase C is reflected in a rapidly 32P-labelled PtdOH pool due to subsequent phosphorylation of the resulting DAG by DAG kinase (Berridge 1992). Similar claims have been made for the green algae Chlamydomonas and Dunaliella (Einspahr et al 1988;Brederoo et al 1991 ;Ha and Thompson1991 ;Musgrave et al 1992) and the same process is presumed to occur in higher plants (Heim and Wagner 1990). In carnation, the rapid incorporation and loss of 32p-label from PtdOH resembles the labelling kinetics of PtdInsP and PtdInsP2, suggesting that the two are again causally related.…”
Section: Discussionmentioning
confidence: 68%
“…From animal systems, we know that extracellular information received by cell surface receptors often activates heterotrimeric G proteins, which in turn activate intracellular effector enzymes that catalyze the formation of second messengers (Gilman, 1987;Birnbaumer et al, 1990;Berridge, 1993;Neer, 1995;Nishizuka, 1995). In recent years, biochemical and molecular analyses have demonstrated that heterotrimeric G proteins are present in plants (reviewed in Ma, 1994), and because their activation has been shown to stimulate effector enzymes and induce physiological responses (Bolwell et al, 1991;Warpeha et al, 1991;Legendre et ai., 1992Legendre et ai., , 1993Musgrave et al, 1992;Quarmby et al, 1992;Neuhaus et al, 1993;Romero and Lam, 1993;White et al, 1993;Yueh and Crain, 1993;Bowler et al, 1994;Cote and Crain, 1994;Elich and Chory, 1994;Ma, 1994;Quarmby and Hartzell, 1994), we assume they play a role in plant cell signaling similar to that described for animals.…”
Section: Introductionmentioning
confidence: 69%
“…A good plant system for studying its possible involvement is the biflagellate green alga Chlamydomonas spp, because there is already convincing evidence for the presence of PLC signaling activity (Irvine et al, 1989Schuring et al, 1990;Brederoo et al, 1991;Dr$bak, 1992Dr$bak, , 1993Musgrave et al, 1992Musgrave et al, ,1993Quarmby et al, 1992;Yueh and Crain, 1993;Cote and Crain, 1994;Munnik et al, 1994aMunnik et al, , 1994bQuarmby and Hartzell, 1994). What is more, this pathway is activated by G protein activators with dramatic effects for gametes; for example, they deflagellate and activate their mating structures, which are two well-established Ca2+ responses (Schuring et al, 1990;Musgrave et al, 1992;Quarmby et al, 1992;Quarmby, 1994;Quarmby and Hartzell, 1994;Sanders and Salisbury, 1994). Using phosphorus-32 to monitor phospholipid turnover, these effects were shown to be correlated with the increased turnover of PtdlnsP2 and a dramatic rise in PtdOH, thought to reflect the phosphorylation of DAG by DAG kinase Quarmby et al, 1992); in retrospect, this rise in PtdOH could be due partially to PLD activity.…”
Section: Mastoparan-stimulated Formation Of Ptdohmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydomonas cells are able to increase the cytoplasmic concentration of calcium either via rhodopsinactivated channels in the cell body, voltage-gated channels on the¯agella (Hartz and Hegemann 1991;Beck and Uhl 1994) or by activating phospholipase C which hydrolyses phosphatidylinositol 4,5-bisphosphate into diacylglycerol (DAG) and inositol-1,4,5-trisphosphate (InsP 3 ; Musgrave et al 1992Musgrave et al , 1993Quarmby and Hartzell 1994). The InsP 3 can then induce the release of calcium from internal stores by binding to the InsP 3 receptor (Berridge 1993).…”
Section: Introductionmentioning
confidence: 99%